2021
DOI: 10.1186/s12903-021-01903-7
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial efficacy of photon-initiated photoacoustic streaming in root canals with different diameters or tapers

Abstract: Background In recent years, the concept of minimally invasive endodontics has been proposed, which could be described as preventing or treating diseases by preserving more dental tissue and creating minimal damage. In the process of root canal preparation, it was recommended to use instruments with a smaller taper to preserve more tooth tissue and improve the preservation rate of the affected teeth. Photon-induced photoacoustic streaming (PIPS) was a new type of laser-activated irrigation techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…[27,28] Our previous study showed ATP level could re ect the amount of bacteria. [11,29,30] And studies also have found that detection techniques based on ATP bioluminescence correlate well with conventional plate counting methods in food testing. [31] The present study showed that the ATP value of the PIPS group was signi cantly lower than that of the CNI group (P = 0.046), indicating that PIPS irrigation had a better bactericidal effect, which coincided with our previous in vitro research.…”
Section: Discussionmentioning
confidence: 90%
“…[27,28] Our previous study showed ATP level could re ect the amount of bacteria. [11,29,30] And studies also have found that detection techniques based on ATP bioluminescence correlate well with conventional plate counting methods in food testing. [31] The present study showed that the ATP value of the PIPS group was signi cantly lower than that of the CNI group (P = 0.046), indicating that PIPS irrigation had a better bactericidal effect, which coincided with our previous in vitro research.…”
Section: Discussionmentioning
confidence: 90%
“…Among these methods, the quantitative ATP technique has proven to be a convenient and rapid tool for assessing live bacteria through the bioluminescence luciferin-luciferase reaction. This approach has also been successfully employed in detecting infected root canals [ 32 34 ]. In addition, in vitro studies have further supported the effectiveness of the PIPS protocol.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we collected dentin shavings to evaluate remaining viable microorganisms. In contrast to sample collections by irrigation or using paper points, this method allowed us to examine bacteria that invaded into dentinal tubules that may not have direct contact with intracanal medication if it does not penetrate well into dentinal tubules [ 44 ]. Our results showed that chitosan paste could significantly reduce viability of both E. faecalis and C. albicans in this root canal biofilm model.…”
Section: Discussionmentioning
confidence: 99%